Борьба за Советы в Омском Прииртышье, (июнь 1918 - нояб. 1919) - Колесников А. Д. (Книжное издательство, 1989)
Экземпляры: КХ (20100506) / Инвентарный номер: 978107 / Цена: 0.50 / Сис.шифр: 63.3(2)712 / Авт.знак: Б 84 / ГРНТИ: 03 / ББК: 63.3(2)612-9